WOMEN VIGILANTES AND OUTLAWS IN AMERICAN POPULAR MEDIA ([S.l.])
1 online resource
Keywords: This interdisciplinary collection of essays examines how women vigilantes, social bandits, outlaws, and anti-heroines were represented in American novels, movie serials, radio dramas, films, comics, and pulp fiction, from the post-Civil War era through World War II.Demonstrating a broad spectrum of methodological and critical approaches, the book includes essays from seasoned as well as emerging scholars. The collected essays fill a gap in present popular culture studies and intersect with outlaw studies, gender studies, feminism, historical studies, and media archaeology, along with citizenship and national identity. The volume also considers how representations of women relate to matters of class, sexuality, and ethnicity. By analyzing female outlaws, both real and imagined, this study highlights the ways that these women have become symbols of justice and social transformation in American cultural memory.This book is an ideal resource for researchers and academics in popular culture studies, media studies, outlaw studies, comparative literature, and feminist studies, as well as historians who focus on media in the late nineteenth and early twentieth centuries.